2011
DOI: 10.1177/0162353211417340
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes of Giftedness in Current and Future Educators

Abstract: This article is a mixed-methods exploration of the levels of stereotypic views about gifted individuals held by current and future educators. Because educators are often asked to provide recommendations for participation in gifted programs, it is important to determine whether those recommendations are based, in part, on stereotypic thinking. Stereotypic views held by educators could bias the selection of participants for gifted programs, preventing students from receiving appropriate gifted educational servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 52 publications
2
30
1
6
Order By: Relevance
“…Because teacher nomination is the most widely required criteria for formal consideration (NAGC, 2015), the gatekeepers of gifted programming often have limited to no knowledge of gifted education—confounding the nomination process with bias and a reliance on ill‐formed and stereotypic beliefs of giftedness (Bain, Bliss, Choate, & Brown, 2007; Berman, Schultz, & Weber, 2012; Carman, 2011; Siegle, Moore, Mann, & Wilson, 2010; Speirs Neumeister, Adams, Pierce, Cassady, & Dixon, 2007). These stereotypic beliefs regarding giftedness are shaped by traditional conceptions of gifted individuals as male (Bianco, Harris, Garrison‐Wade, & Leech, 2009; Carman, 2011), White or Asian (Carman, 2011; Ford et al, 2008), as displaying academic characteristics valued by the dominant Eurocentric culture which rewards behaviors like leadership (Siegle et al, 2010) and the intrinsic motivation to learn (Speirs Neumeister et al, 2007), and the false notion that gifted students are a homogenous group with the ability to thrive in the absence of targeted academic interventions (Reis & Renzulli, 2009). Despite significant research exploring the problems inherent in this process, nomination remains the most common method of referring students for formal identification nationwide (NAGC, 2015).…”
Section: Insufficient Educator Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Because teacher nomination is the most widely required criteria for formal consideration (NAGC, 2015), the gatekeepers of gifted programming often have limited to no knowledge of gifted education—confounding the nomination process with bias and a reliance on ill‐formed and stereotypic beliefs of giftedness (Bain, Bliss, Choate, & Brown, 2007; Berman, Schultz, & Weber, 2012; Carman, 2011; Siegle, Moore, Mann, & Wilson, 2010; Speirs Neumeister, Adams, Pierce, Cassady, & Dixon, 2007). These stereotypic beliefs regarding giftedness are shaped by traditional conceptions of gifted individuals as male (Bianco, Harris, Garrison‐Wade, & Leech, 2009; Carman, 2011), White or Asian (Carman, 2011; Ford et al, 2008), as displaying academic characteristics valued by the dominant Eurocentric culture which rewards behaviors like leadership (Siegle et al, 2010) and the intrinsic motivation to learn (Speirs Neumeister et al, 2007), and the false notion that gifted students are a homogenous group with the ability to thrive in the absence of targeted academic interventions (Reis & Renzulli, 2009). Despite significant research exploring the problems inherent in this process, nomination remains the most common method of referring students for formal identification nationwide (NAGC, 2015).…”
Section: Insufficient Educator Preparationmentioning
confidence: 99%
“…Speirs Neumeister et al (2007) found that potential characteristics of giftedness suggested to be more prevalent in certain minority groups (e.g., “oral tradition, movement and verve, communalism” in African‐American students) are less likely to be associated with giftedness by educators (p. 486). Unfortunately, preconceived ideas about giftedness shape what educators expect to see in the classroom (Berman et al, 2012; Carman, 2011). Research suggests that race and ethnicity inform the expectations of preservice and in‐service teachers who lack gifted‐specific training (Carman, 2011).…”
Section: Deficit Thinking and Teacher Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ένα τμήμα του μαθητικού πληθυσμού που λαμβάνει εκπαίδευση αλλά συνήθως δεν είναι ανάλογη των ικανοτήτων του, είναι οι χαρισματικοί. Στο παρελθόν κυρίως αλλά και σήμερα, τα χαρισματικά άτομα λόγω των δεξιοτήτων τους έρχονται αντιμέτωπα με προκαταλήψεις και στερεότυπα που είναι βαθιά ριζωμένα στις συνειδήσεις των κοινωνιών (Carman, 2011. Matthews, Ritchotte, & Jolly, 2014 .…”
Section: εκπαιδευση και χαρισματικοτηταunclassified